2008
DOI: 10.3746/jkfn.2008.37.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citrus junos Peel on the Quality and Antioxidant Activity of Traditional Rice Wine, Jinyangju

Abstract: The quality and antioxidant activity properties of Jinyangju, Korean traditional rice wine made with different additions of Citrus junos peel (0, 10, 20, 30, and 40%) were investigated. The pH and the total sugar content of the Jinyangju decreased, whereas the total acidity and alcohol content increased with greater additions of Citrus junos peel. The color L-value increased and the color a-and b-values decreased with increasing amounts of Citrus junos peel. The DPPH (1,1-diphenyl-2-picryl-hydrazyl) free radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 5 publications
1
5
0
3
Order By: Relevance
“…The alcohol content of mulberry yakju rapidly increased between 3 and 5 d of fermentation, and then slightly increased in the following order: control yakju (13.0%) > CP yakj u (12.0%) > SP yakju (10.0%) > DP yakju (9.0%) on the 15th day of fermentation (Figure 2C). This result is in agreement with several previous reports, which found that the alcohol content of the control yakju was higher than that of yakju containing grapes (Lee and Kwak 2011) and Citrus junos peel (Jin and others 2008). This effect was attributed to the inhibition of microbial growth due to the high polyphenol content of the grapes, Citrus junos peels, and mulberry (Radovanović and others 2009).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The alcohol content of mulberry yakju rapidly increased between 3 and 5 d of fermentation, and then slightly increased in the following order: control yakju (13.0%) > CP yakj u (12.0%) > SP yakju (10.0%) > DP yakju (9.0%) on the 15th day of fermentation (Figure 2C). This result is in agreement with several previous reports, which found that the alcohol content of the control yakju was higher than that of yakju containing grapes (Lee and Kwak 2011) and Citrus junos peel (Jin and others 2008). This effect was attributed to the inhibition of microbial growth due to the high polyphenol content of the grapes, Citrus junos peels, and mulberry (Radovanović and others 2009).…”
Section: Resultssupporting
confidence: 94%
“…In general, the alcohol content of yakju increases from 10% to 18% after 4 to 5 d of fermentation at 25 °C, and it can be used as an alcoholic beverage. However, to improve the flavor and color or extraction of functional compounds, yakju needs to be fermented for more than 5 to 15 d (Jin and others 2008; Kim and others 2008a). Recently, Korean consumers have had an increase in demand for high quality yakju with functionality and preference properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…유자의 구성은 껍질, 육질, 종실 등으로 크게 나눌 수 있는데, 이들 중 껍질은 두껍고 표면이 울퉁불퉁하며 전체 과실의 약 40-45% 정도를 차지하고 향기성분, 섬유소, 플라 보노이드 등이 비교적 많이 함유되어 있다 (8)(9)(10). 이러한 유자껍질의 활용성 증대를 위한 연구로는 올레오레진, 소 시지, 쿠키, 진양주, 막걸리 등의 제조 (11)(12)(13)(14)(15)에 관한 것이 수행된 바 있으며, 또한 유자껍질 열수추출물이 강한 항산 화능을 가지는 것으로 밝혀져 이의 음용차 원료로서 높은 가치를 인정받았다 (4). 음용차는 약용 및 기호성 식물체로 부터 유효성분을 섭취하기 위한 수단으로 원료를 건조한 후 열수에 우리거나 타서 마시는 식품형태이다 (16).…”
unclassified
“…함에 따라 높았다. 이는 유자 과피를 첨가하여 제조한 진양주의 품질 및 항산화 특성 변화와 비슷한 경향을 보였다(34).으름 첨가 막걸리의 총균수 변화으름열매를 첨가하여 제조한 막걸리의 발효 중 총균수의 변화 를 측정한 결과는Table 1에 나타내었다. 담금 직후 대조군에서 는 9.2×10 4 CFU/mL, 으름 첨가군 1%에서는 9.7×10 4 CFU/mL , 으름 첨가군 3%에서는 7.5×10 4 CFU/mL, 으름 첨가군 5%에서는 8.6×10 4 CFU/mL, 으름 첨가군 7%에서는 1.0×10 5 CFU/mL으로 나 타났다.…”
unclassified